LOW-SALT DIETARY INTAKE REDUCES HUNGER IN PATIENTS WITH CHRONIC RENAL FAILURE. - Lestari, Agustina; Apriyanti, Rita; Negara, Candra Kusuma (Sean Institute, 2022)
The hardest part for patients is adhering to fluid intake restrictions, which can be stressful to the point that patients cannot regulate their fluid intake consumption. The main factor determining the effectiveness of hemodialysis is the patient's adherence to the rules on food and fluid intake. This study aims to determine whether controlling food intake affects how much salt a patient receiving hemodialysis for chronic renal failure feels like they are thirsty. This study is quasi-experimental, using a pre-post test, a control group, successive sampling for sample selection, and up to 15 samples for each intervention and control group. A thirst distress scale (TDS) questionnaire and a visual analog scale (VAS) were used to gauge the respondents' thirst levels. In contrast, the Wilcoxon test and the Mann-Withney test with a significance level of p 0.05 were used in the data analysis for this investigation. There was a difference in thirst as measured by TDS with a meaning fulness of p = 0.008 (p0.05) and VAS with a meaning of p + 0.048 (p0.05) after the intervention, according to the results, which showed that 13 respondents experienced a decrease in TDS values and two people whose TDS values remained with the meaningfulness of 0.000 (p0.05) after treatment in the intervention group. The results of this study allow us to conclude that education is provided continuously. A patient's daily self-care behavior can be improved by the conduct of home visits as a form of supervision of the education that has been given. This behavior includes reducing the patient's daily salt intake to lessen the thirst patients with renal failure receiving hemodialysis frequently experience.